2006
DOI: 10.1007/s11099-005-0172-1
|View full text |Cite
|
Sign up to set email alerts
|

Newly-formed photosynthates and the respiration rate of girdled stems of Korean pine (Pinus koraiensis Sieb. et Zucc.)

Abstract: A stem-girdling experiment was carried out on an evergreen conifer, the Korean pine (Pinus koraiensis Sieb. et Zucc.), in mid summer in Northeast China. A 50 % higher respiration rate at the upper part of the stem was observed 3 d after stem girdling, and a stable higher rate (1.2-2.8 times) one week later. However, no higher soluble sugar or starch contents were found in the upper bark of the girdled stems in measurements over three weeks. These findings indicate that most of the newly-formed photosynthates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
3
11
0
Order By: Relevance
“…This newly formed assimilating tissue might also explain why the starch content tended to increase in L after girdling. Such an increase was never observed before in other girdling experiments (Li et al, 2003;Daudet et al, 2005;Wang et al, 2006).…”
Section: Discussion Double Girdling Affects Both the Carbon And Watersupporting
confidence: 61%
“…This newly formed assimilating tissue might also explain why the starch content tended to increase in L after girdling. Such an increase was never observed before in other girdling experiments (Li et al, 2003;Daudet et al, 2005;Wang et al, 2006).…”
Section: Discussion Double Girdling Affects Both the Carbon And Watersupporting
confidence: 61%
“…Across the species measured, stem temperature explained from 31 to 66% of the variation in E S during the dormant season, but only 1-20% in the growing season. Among the factors that influence E S during the growing season, but are not present in the dormant season, are growth respiration, which is considered temperature independent (Thornley and Johnson 1990), the flux of transported CO 2 in xylem sap Aubrey and Teskey 2009), current photosynthate supply (Wang et al 2006b;Wittmann and Pfanz 2008). Similar to our results, Zach et al (2010) found that for trees in tropical montane forest, E S was independent from T S in the wet season, but was well correlated with T S in the dry season.…”
Section: Discussionmentioning
confidence: 99%
“…Cernusak et al (2006) found that R stem declined in several tropical savanna tree species following fire disturbance that reduce canopy leaf area. Wang et al (2006) showed that the magnitude of diel R stem in Pinus koraiensis Sieb. & Zucc.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon availability via canopy photosynthesis is tightly linked to stem and soil CO 2 efflux (Tang et al 2005). Stem CO 2 efflux declined when substrate availability was experimentally manipulated by altering the supply of photosynthates (Edwards et al 2002) through stem girdling (Edwards and McLaughlin 1978;Martin et al 1994;Lavigne et al 2004;Wang et al 2006;Maier et al 2010), pruning (Maier and Clinton 2006), or canopy scorching (Cernusak et al 2006). Cernusak et al (2006) attributed lower rates of stem CO 2 efflux following burning to reductions in canopy photosynthesis.…”
Section: Introductionmentioning
confidence: 99%